Assessment of the core and support functions of the Integrated Disease Surveillance system in Maharashtra, India - Phalkey, Revati; Shukla, Sharvari; Shardul, Savita; Ashtekar, Nutan; Valsa, Sapna; Awate, Pradip; Marx, Michael (BMC public health, 2013)
Monitoring the progress of the Integrated Disease Surveillance (IDS) strategy is an important component to ensure its sustainability in the state of Maharashtra in India. The purpose of the study was to document the baseline performance of the system on its core and support functions and to understand the challenges for its transition from an externally funded “project” to a state owned surveillance “program”.
Gesehen am 24.01.2022